Minerals of the mercury ore deposit Idria - Recnik, Aleksander; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
The present work is the first comprehensive study of mineralogy of the world's second largest mercury mine Idria. In the first chapter the readers are acquainted with the history of mining and its relation to mineralogy. Mineralogy is explained in terms of geological processes that were active during the formation of the ore deposit. Among these, hydrocarbons present in the host rocks play a very important role during crystallization. The central part of the book is dedicated to the main mineral of the ore deposit, cinnabar. It occurs in a variety of crystal forms, of which the most special are lateral interpenetration twins. The book is written for a broad readership, and will be interesting for geologists, mineralogist and crystallographers, as well as for those interested in the history of mineral collecting in Idria.
Introduction -- The History of Mining -- Geology and Formation of the Ore Deposit (UH) -- Mercury Ores -- Minerals of the Idrija Ore Deposit -- Native Mercury -- Hydrocarbons and Idrialine -- Pyrite and other Sulfide Minerals -- On the Idrija Cinnabar -- Twinning of Cinnabar -- Mineralogical Expedition -- Metacinnabar and Calcite -- Dolomite and Quartz -- Silicate Minerals -- Baryte and Celestine -- Minerals of the Oxidation Zone -- Geological and Technical Heritage of Idrija (BR) -- References.
Keywords: Mineral resources; Mineralogy; Economic geology; Mineral Resources; Mineralogy; Economic Geology